2020
DOI: 10.1371/journal.pone.0239278
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ and Grandmothers’ misconceptions and socio-cultural factors as barriers to exclusive breastfeeding: A qualitative study involving Health Workers in two rural districts of Ghana

Abstract: Background Education on exclusive breastfeeding (EBF) practices is usually given in the form of health talks by health workers (HWs). The need for HWs to be well-informed about cultural practices and misconceptions that act as barriers to EBF has been documented in literature. This information can guide HWs in developing interventions such as health talks which are culturally sensitive. However, this has not been explored from the perspectives of HWs in Ghana. In this paper, we report mothers' and grandmothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
5
27
0
4
Order By: Relevance
“…The results from this study is in line with the previous study reported that weaning at 2 years of age is beneficial for the child, mom, and whole families [9][10][11][12]. Negative impact caused by early weaning, according to Quran expert, is not always considered as negative since breastfeeding practice needs consents and supports from both parents of the child and whole family [13][14][15]. It considers ability from the mother to breastfed and whole family to support.…”
Section: Development Of Weaning Indexsupporting
confidence: 89%
“…The results from this study is in line with the previous study reported that weaning at 2 years of age is beneficial for the child, mom, and whole families [9][10][11][12]. Negative impact caused by early weaning, according to Quran expert, is not always considered as negative since breastfeeding practice needs consents and supports from both parents of the child and whole family [13][14][15]. It considers ability from the mother to breastfed and whole family to support.…”
Section: Development Of Weaning Indexsupporting
confidence: 89%
“…Studies have also documented the traditional practice of giving herbal concoctions to infants to drink after birth, especially in the Northern part of Ghana. It is perceived that herbal concoctions make the infants strong and healthy [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In counseling without being based on the the Leininger's Transcultural, counseling was only given to postpartum mothers so that only postpartum mothers understand exclusive breastfeeding, while parents as decision-makers were not involved. This condition caused families to tend to provide negative support to postpartum mothers (9) . The form of non-probreastfeeding support that was often done by mothers was to encourage postpartum mothers to give formula milk on days 1 and 2 because the production of milk was less according to the family (10) .…”
Section: Discussionmentioning
confidence: 99%
“…The form of non-probreastfeeding support that was often done by mothers was to encourage postpartum mothers to give formula milk on days 1 and 2 because the production of milk was less according to the family (10) . Another mistaken belief was that babies gained weight rapidly when fed on infant formulas (9) . The family does not understand that colostrum production was in accordance with the needs of the baby and the size of the baby's stomach with a capacity of ± 5 cc.…”
Section: Discussionmentioning
confidence: 99%